Identifikasi Kelengkapan Pengisian Rekam Medis Elektronik Pasien Rawat Inap di RSKD Duren Sawit Jakarta Tahun 2022 - Munazhifah Munazhifah; Noor Yulia; Deasy Rosmala Dewi; Puteri Fannya (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Medical records must be made in writing, complete, and clear or electronically. Electronic health record is an electronic medical record which is an access in managing patient health information that is generated every time a patient accesses medical care. Medical records must be completed within 24 hours with a 100% completeness percentage. This study aims to determine the percentage of completeness of electronic medical records of inpatients at Duren Sawit Hospital, Jakarta. The research method uses a descriptive method with a quantitative analysis approach. A sample of 77 electronic medical records of inpatients uses a purposive sample (consideration sample). The results of the study: there is no Standard Operating Procedure for Electronic Medical Records that serves as a guide in working. From the analysis, it was found that the completeness of filling was 84% ​​and the incompleteness was 16%. It has not reached the minimum standard that has been set by the Ministry of Health, which is 100%. (The most complete component is the patient identity component with a percentage of 100%, while the lowest completeness is an important report component 65%). Several factors cause incomplete medical records, namely: The large number of patients, senior doctors who do not understand technology, and computer systems and networks that sometimes error/down. Suggestions are made for Standard Operating Procedures for filling out Electronic Medical Records, mentoring and socializing to senior doctors and officers contacting related parties so that they can complete medical records immediately (< 24 hours).